Identifikasi Dampak dan Strategi Dalam Mereduksi Fenomena Urban Heat Island di Kawasan Metropolitan Jabodetabek - Mh Nateq Nouri; Dinan, Rois (REKA RUANG, 2024)
Jabodetabek is a metropolitan area where DKI Jakarta serves as the center of government and economy in Indonesia. As a hub of activities in Indonesia, its operations are inherently more complex than in other locations. Individuals from outside DKI Jakarta are drawn to migrate to the region due to its intricate activities. Covering an area of 15,978 km2, DKI Jakarta had the highest population density among Indonesian provinces in 2021. This high population density can have environmental implications, leading to the phenomenon of the Urban Heat Island (UHI). The density of buildings, driven by the substantial population, contributes to elevated surface temperatures, exacerbated in situations with low green spaces or minimal vegetative cover. Hence, the aim of this research is to determine the impact of the UHI phenomenon in DKI Jakarta on its surrounding areas (Bodetabek) and propose methods to mitigate these effects. To identify the UHI phenomenon, the researchers utilized LST and NDVI analysis methods to measure vegetation density, along with NDBI to gauge building density. The research adopted a Willingness to Pay (WTP) approach for DKI Jakarta and Bodetabek, creating spatial strategies to reduce environmental impact. The analysis results reveal that East Jakarta experiences the most severe UHI phenomenon, while Bogor Regency has the lowest surface temperatures. Concerning the willingness to pay for environmental services, the average Willingness to Pay (WTP) value from 104 respondents in DKI Jakarta is approximately Rp. 66,846.00. The CVM results indicate a value of 62%, signifying a strong relationship between the observed variables. Thus, these findings suggest that respondents possess a significant willingness to pay for environmental improvement in the area. The analysis outcomes indicate that stakeholders involved can implement the POAC strategy outlined in this research.